(untitled) (SCIENCE TIME JOURNAL, 2025)
This study investigates the translation of lexical units employed in emergency contexts, with particular emphasis on the English and Uzbek languages. Through a mixed-methods approach incorporating systematic literature review, comparative textual analysis of parallel corpora, and semi-structured interviews with professional translators, the research identifies key challenges inherent to crisis communication translation. The findings reveal that emergency lexicon is characterized by a high degree of functionality, semantic density, and imperative modality, necessitating translation strategies that prioritize functional equivalence over formal correspondence. Primary obstacles include conceptual gaps for terms like “shelter in place” and “triage,” cultural-pragmatic mismatches in directive force, and the tension between urgency and precision. The study proposes a model emphasizing collaborative translation, pre-established terminology databases, and multimodal adaptation to enhance the efficacy of risk communication in cross-cultural settings. This research contributes to the growing field of crisis linguistics and provides practical guidelines for translators and humanitarian organizations operating in Central Asia.